Electoral violence and the legacy of authoritarian rule in Kenya and Zambia. (January 2020) - Brosché, Johan; Fjelde, Hanne; Höglund, Kristine
Why do the first multiparty elections after authoritarian rule turn violent in some countries but not in others? This article places legacies from the authoritarian past at the core of an explanation of when democratic openings become associated with electoral violence in multi-ethnic states, and complement existing research focused on the immediate conditions surrounding the elections. We argue that authoritarian rule characterized by more exclusionary multi-ethnic coalitions creates legacies that amplify the risk of violent elections during the shift to multiparty politics. Through competitive and fragmented interethnic relations, exclusionary systems foreclose the forging of cross-ethnic elite coalitions and make hostile narratives a powerful tool for political mobilization. By contrast, regimes with a broad-based ethnic support base cultivate inclusive inter-elite bargaining, enable cross-ethnic coalitions, and reduce incentives for hostile ethnic mobilization, which lower the risk of violent elections. We explore this argument by comparing founding elections in Zambia (1991), which were largely peaceful, and Kenya (1992), with large-scale state-instigated electoral violence along ethnic lines. The analysis suggests that the type of authoritarian rule created political legacies that underpinned political competition and mobilization during the first multiparty elections, and made violence a more viable electoral strategy in Kenya than in Zambia.